MR findings in oculocerebrorenal syndrome. - Carroll, W J; Woodruff, W W; Cadman, T E (American Journal of Neuroradiology, 1993)
Oculocerebrorenal syndrome is an X-linked recessive disorder characterized by congenital ocular abnormalities, mental retardation, renal disease, and metabolic bone disease. We report a case of oculocerebrorenal syndrome and, using T1-, proton density-, and T2-weighted imaging sequences, are able to characterize two distinct white matter abnormalities: one lesion is punctate and has signal characteristics that parallel that of cerebrospinal fluid; a second lesion, found in association with the first, consists of patchy white matter abnormalities that are hypointense on T1-weighted images but hyperintense on proton density- and T2-weighted images.